Breastfeeding mobile application for mothers with gestational diabetes mellitus: designed by mothers and experts - Seungmi Park; Eunju Kwak; Jisan Lee (BMC, 2022)
Abstract Background Mothers and babies with gestational diabetes have an increased risk of diabetes, obesity, and cardiovascular complications. Breastfeeding is known to help reduce complications in mothers and babies with gestational diabetes. However, the rate of breastfeeding among mothers with gestational diabetes is still low due to various barriers. Therefore, the purpose of this study was to develop a mobile application to improve the breastfeeding barrier of pregnant women with gestational diabetes. Methods The Method of App Selection based on Users' Needs is a method used in designing app structure and user interface by considering user needs. This method was used to develop the Breastfeeding for Gestational Diabetes Mellitus App, reflecting the needs of target users. Four personas were created based on the experiences of four mothers with gestational diabetes mellitus, and these personas' needs were assessed and prioritized. Two professors and a clinical instructor in women's health nursing conducted an expert review and revised the contents. Results Our "Breastfeeding for Gestational Diabetes Mellitus App" included the following components to promote breastfeeding in mothers with gestational diabetes mellitus: baby growth, breastfeeding records, information about mothers with gestational diabetes mellitus, information about breastfeeding, videos demonstrating breastfeeding methods and breast massage techniques, breastfeeding success stories, a message board, a section for frequently asked questions and answers, and links to breastfeeding education centers. Conclusions Use of our App is expected to help prevent complications in mothers with diabetes mellitus and their babies and to promote maternal and child health through improved breastfeeding practices, especially in social distancing situations resulting from COVID-19.